Brain hemispheres with right temporal lobe damage swap dominance in early auditory processing of lexical tones - Wei, Yarui; Liang, Xiuyuan; Guo, Xiaotao; Wang, Xiaoxiao; Qi, Yunyi; Ali, Rizwan; Wu, Ming; Qian, Ruobing; Wang, Ming; Qiu, Bensheng; Li, Huawei; Fu, Xianming; et al. (Frontiers in Neuroscience, 2022)
Labor division of the two brain hemispheres refers to the dominant processing of input information on one side of the brain. At an early stage, or a preattentive stage, the right brain hemisphere is shown to dominate the auditory processing of tones, including lexical tones. However, little is known about the influence of brain damage on the labor division of the brain hemispheres for the auditory processing of linguistic tones. Here, we demonstrate swapped dominance of brain hemispheres at the preattentive stage of auditory processing of Chinese lexical tones after a stroke in the right temporal lobe (RTL). In this study, we frequently presented lexical tones to a group of patients with a stroke in the RTL and infrequently varied the tones to create an auditory contrast. The contrast evoked a mismatch negativity response, which indexes auditory processing at the preattentive stage. In the participants with a stroke in the RTL, the mismatch negativity response was lateralized to the left side, in contrast to the right lateralization pattern in the control participants. The swapped dominance of brain hemispheres indicates that the RTL is a core area for early-stage auditory tonal processing. Our study indicates the necessity of rehabilitating tonal processing functions for tonal language speakers who suffer an RTL injury.